Characteristics of Nursing Home Resident Movement Patterns: Results from the TEAM-UP Trial. (May 2022) - Kennerly, Susan M.; Sharkey, Phoebe D.; Horn, Susan D.; Zheng, Tianyu; Alderden, Jenny; Sabol, Valerie K.; Rowe, Meredeth; Yap, Tracey L.
ABSTRACT: OBJECTIVE: To determine movement patterns of nursing home residents, specifically those with dementia or obesity, to improve repositioning approaches to pressure injury (PrI) prevention. METHODS: A descriptive exploratory study was conducted using secondary data from the Turn Everyone And Move for Ulcer Prevention (TEAM-UP) clinical trial examining PrI prevention repositioning intervals. K-means cluster analysis used the average of each resident's multiple days' observations of four summary mean daily variables to create homogeneous movement pattern clusters. Growth mixture models examined movement pattern changes over time. Logistic regression analyses predicted resident and nursing home cluster group membership. RESULTS: Three optimal clusters partitioned 913 residents into mutually exclusive groups with significantly different upright and lying patterns. The models indicated stable movement pattern trajectories across the 28-day intervention period. Cluster profiles were not differentiated by residents with dementia (n = 450) or obesity (n = 285) diagnosis; significant cluster differences were associated with age and Braden Scale total scores or risk categories. Within clusters 2 and 3, residents with dementia were older ( P < .0001) and, in cluster 2, were also at greater PrI risk ( P < .0001) compared with residents with obesity; neither group differed in cluster 1. CONCLUSIONS: Study results determined three movement pattern clusters and advanced understanding of the effects of dementia and obesity on movement with the potential to improve repositioning protocols for more effective PrI prevention. Lying and upright position frequencies and durations provide foundational knowledge to support tailoring of PrI prevention interventions despite few significant differences in repositioning patterns for residents with dementia or obesity.